2017
DOI: 10.1038/ijo.2017.187
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal fat deposits determined by magnetic resonance imaging in relation to leptin and vaspin levels as well as insulin resistance in the general adult population

Abstract: SAT and LFC were identified as predominant sites associated with leptin and vaspin levels, respectively. Residual analysis pointed towards a general adverse effect of disproportional triglyceride storage across physiological despots, in particular in ectopic sides such as the liver, with markers of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
2
20
1
1
Order By: Relevance
“…In line with our results, these studies have mainly presented inverse associations of SAT and VAT with adiponectin (17,18), as well as positive associations with leptin (10,17,18) and chemerin concentrations (4). The contribution of LFC to circulating adipokine concentrations was addressed in only a few studies that reported conflicting results (10,18). Differences in Figure 4 (A) Beta estimates from linear regression analyses (n = 4,116) for the associations of circulating adipokine concentrations with different metabolic parameters and blood pressure as well as (B) odds ratios from logistic regression analyses (n = 4,116) for the associations between circulating adipokine concentrations and metabolic syndrome (MetS) as well as its components.…”
Section: Fat Deposits and Adipokinessupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our results, these studies have mainly presented inverse associations of SAT and VAT with adiponectin (17,18), as well as positive associations with leptin (10,17,18) and chemerin concentrations (4). The contribution of LFC to circulating adipokine concentrations was addressed in only a few studies that reported conflicting results (10,18). Differences in Figure 4 (A) Beta estimates from linear regression analyses (n = 4,116) for the associations of circulating adipokine concentrations with different metabolic parameters and blood pressure as well as (B) odds ratios from logistic regression analyses (n = 4,116) for the associations between circulating adipokine concentrations and metabolic syndrome (MetS) as well as its components.…”
Section: Fat Deposits and Adipokinessupporting
confidence: 92%
“…However, previous studies, which dealt with circulating adipokine concentrations in relation to behavioral risk factors and metabolic phenotypes in humans, mostly included only a small number of participants (2,3), just observed selected patient cohorts (2,3), or concentrated only on one or two specific adipokines (2,6,8). Furthermore, only a few human studies have investigated associations of circulating adipokine concentrations with fat deposits (2,4,10).…”
Section: Original Articlementioning
confidence: 99%
“…In this same study, leptin was not independently related to abdominal fat distribution and the authors concluded that circulating leptin climbs continuously with increasing adiposity [38]. A more recent study showed a strong positive association between subcutaneous adipose tissue and leptin levels, but not visceral adipose tissue nor liver fat content and leptin, independent of the HOMA-IR status [39]. Our finding of increased risk of type 2 diabetes with increased levels of leptin observed among abdominally non-obese participants adds weight to the "leptin resistance' phenomenon in the context of a large population sample.…”
Section: Discussionmentioning
confidence: 78%
“…[38] A more recent study showed a strong positive association between subcutaneous adipose tissue and leptin levels, but not visceral adipose tissue nor liver fat content and leptin, independent of the HOMA-IR status. [39] Our finding of increased risk of type 2 diabetes with increased levels of leptin observed among abdominally non-obese participants adds weight to the "leptin resistance' phenomenon in the context of a large population sample.…”
Section: Discussionmentioning
confidence: 57%